Prototype Framework for Dynamic Probabilistic Risk Assessment of Space-Flight Medical Events - Pajunen, Kirsti (Proceedings of the Wisconsin Space Conference, 2012)
Medical problems in space, while not necessarily common, can be life and mission threatening. Because of this, a model has been created to assess the risk of certain medical events under space mission conditions called the Integrated Medical Model (IMM). The model uses a type of risk analysis called Probabilistic Risk Assessment. An effort is being conducted to convert these static models to Dynamic PRA (DynaPRA) models. These models would integrate changing conditions in space missions such as human interaction, changing system components, and environmental factors and apply a risk analysis to find more complete and useful probabilities of certain medical events occurring to astronauts in space. To this end, a prototype DynaPRA framework was created during the first three months of the project using the existing IMM hip, wrist, and lumbar spine bone fracture models as a case study. After the initial implementation was complete, ideas were generated for applying this framework to the rest of the IMM.Â